Canons in Media Language and Professional Voice - Hernández-Campoy, Juan M.; Cutillas-Espinosa, Juan A. (Complutense Journal of English Studies, 2017)
Linguistic prescriptivism is an ideology and authority based practice that has traditionally vindicated the use of norms of language as social conventions on correctness, appropriateness, aesthetics and validity, also affecting media language. The aim of this paper is to explore the theoretical underpinnings of the Script Design model, which underlines the need to consider not only responsive and even initiative based performance, but also the script or use of a professional voice, as part of structural constrains, that conditions the individual linguistic behaviour in public occupations. The debate on responsive-initiative motivations in stylistic variation is a central issue of the traditional pendulum-oscillating di-lemma in social theory about the relationship between structure and agency, i.e. between sociolinguistic limitations and creativity, and also between speaker intention and listener understanding. Despite their social or regional background, speakers modify their linguistic production in public depending on the market characteristics and the structural constrains. The spirit of the Script Model, therefore, alludes to the standing debate in both classical and contemporary sociological theory over the primacy of social structure or agency in shaping human behaviour and the meaning of human behaviour itself.